Intestinal Amebiasis in Children with Bloody Diarrhea - Budi Purnomo; Badriul Hegar (The Indonesian Society for Digestive Endoscopy, 2011)
Background: Amebiasis affects more than 50 million people each year, resulting in 100,000 deaths. Entamoeba histolytica (E. histolytica) is clearly pathogenic causing intestinal infection that varies from asymptomatic to fulminant colitis. Appropriate diagnosis and treatment of amebiasis in children is important to avoid serious complication, such as hepatic abscesses. Bloody diarrhea is a classic symptom, which is often used as screening for intestinal amebiasis. This study aimed to know the prevalence of intestinal amebiasis and other clinical and laboratory characteristics in children with bloody diarrhea who visited Harapan Kita Women and Children Hospital, Jakarta. Method: This was a retrospective descriptive study. Data was obtained by evaluating medical records at Harapan Kita Women and Children Hospital Jakarta, from January 2009 to December 2010. The data included age, sex, morphology of E. histolytica, blood hemoglobin level and leukocyte count, as well as fecal leukocytes and erythrocytes. Diagnosis was confirmed by finding trophozoites in 3 consecutive stool specimens. Statistical analysis was performed using SPSS program. Results: Trophozoite forms were found in 58/889 (6.5%) children with bloody diarrhea. There were 40 (58.8%) boys, and 27 (39.7%) children were ≤ 1 years old. Fourteen (20.6%) children had anemia, 49 (72.1%) children had fecal leukocytes 10 and 51 (75%) children had fecal erythrocytes 5; however, only 21 (30.9%) children with blood leukocytes count 14,000 u/L. Conclusion: Intestinal amebiasis is common in children with bloody diarrhea, especially infants. Increased fecal leukocytes and erythrocytes are often found in intestinal amebiasis; however, blood leukocyte count may not increase. Keywords: children, intestinal tract, amebiasis